Fenomena Belajar Agama Generasi Millenial: Studi Kasus Pada Mahasiswa Fakultas Sains di Perguruan Tinggi Keagamaan Islam - Syam, Abdi Mubarak; Prasetiya, Nurul Huda (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2022)
The millennial generation of Muslims is often identified with popular culture with instant characteristics and tends to be technologically related. In 'consuming' religious teachings, according to several studies, they use these characteristics, namely learning religion quickly, instantly and without going through a diligent learning process, with teachers or through formal education. The era of technological development is also used as a tool in learning religion. The purpose of this study is to describe how access to religious information is among students of the Faculty of Science at Islamic Universities in Medan. This is because almost 90% of students in the faculty come from a public school education background and then study at Islamic universities which of course are involved in the study of Islamic discourses. This study uses a qualitative research method with a descriptive analysis approach. The result is that religious access or more precisely religious references are obtained through an instant process, namely learning from WhatsApp application groups, YouTube and social media such as Facebook. The conclusion in this study is that digital literacy is needed as a set of knowledge to be more critical, analytical and evaluative in understanding existing religious information.